1 Answer | Add Yours
To simplify `i^n` , divide the exponent by 4. Then, consider only the remainder of the quotient.
>> If remainder is 0 ,then `i^n=1` .
>> If reminder is 1, then `i^n=i` .
>> If remainder is 2, then `i^n=-1` .
>> If remainder is 3, then `i^n=-i` .
Applying this, the remainder of `i^13` is:
13 `-:` 4 = 3 Remainder 1
Hence, `i^13=i` .
Another way is to breakdown `i^13` to factors of `i^4` .
Since `i^4=1` , then
Thus, either method results to `i^13=i` .
We’ve answered 319,630 questions. We can answer yours, too.Ask a question